2015
DOI: 10.1007/s11069-015-1588-y
|View full text |Cite
|
Sign up to set email alerts
|

The M w 6.9 Sikkim–Nepal earthquake of September 2011: a perspective for wrench faulting in the Himalayan thrust zone

Abstract: In the present study, we analyze the strike-slip-type earthquakes along the Himalayan arc that are transverse to the collision front, with a special emphasis on the Sikkim region. The study examines seismicity and focal mechanism data in conjunction with crustal structure derived from receiver functions and gravity gradients, supported by results from GPS data. We present a relation between the north-south depth distribution of the strike-slip earthquakes in Sikkim, with the northward dipping trend of the Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Deep‐seated lineaments parallel to the edges of the Delhi‐Haridwar, Faizabad, and Munger‐Saharsa ridges represent surfaces that extend as deep as the base of the Indian lithosphere (Godin & Harris, 2014), and in the case of several ridges, appear to show opposing senses of dip. Several mapped basement faults align with these lineaments, including the Great Boundary, Lucknow, Kishangang, and West/East Patna Faults (Godin & Harris, 2014; Rao et al., 2015; Valdiya, 1976). Some of these faults have been interpreted to be active based on observations of recent soft sediment deformation structures (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Deep‐seated lineaments parallel to the edges of the Delhi‐Haridwar, Faizabad, and Munger‐Saharsa ridges represent surfaces that extend as deep as the base of the Indian lithosphere (Godin & Harris, 2014), and in the case of several ridges, appear to show opposing senses of dip. Several mapped basement faults align with these lineaments, including the Great Boundary, Lucknow, Kishangang, and West/East Patna Faults (Godin & Harris, 2014; Rao et al., 2015; Valdiya, 1976). Some of these faults have been interpreted to be active based on observations of recent soft sediment deformation structures (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Kumar et al [2012] inferred eclogitization of the lower crust in the Sikkim and southern Tibet regions wherein jelly sandwich model could explain seismogenesis by assuming a strong lower crust and up-per mantle. Rao et al [2015] used receiver function analysis and suggested that transverse faults caused by thrust partitioning along the Himalayan arc manifest as vertical strike-slip faults cutting across the crust of the descending Indian plate down to 60 km. de la Torre et al [2007] suggested that in the eastern Nepal and Tibet region, strike-slip earthquakes at depths of 70-100 km and thrust earthquakes at shallower depths could be attributed to Indian plate convergence accommodated through shear along vertical fault planes that extend to Moho depths.…”
Section: Discussionmentioning
confidence: 99%
“…However, comprehensive aftershock studies using temporary networks are carried out for the recent damaging earthquakes since 1991. These significant earthquakes are the 1991 Uttarkashi (M w 6.3) and 1999 Chamoli (M w 6.3) earthquakes in the western Himalaya, the 1993 Latur (M w 6.3), the 1997 Jabalpur (M w 6.0) and the 2001 Bhuj (M w 7.7) earthquakes in peninsular India, the 2002 Andaman (M w 6.5) and the 2004 Sumatra (M w 9.3) earthquakes in the subducting Indian oceanic plate, the 2005 Kashmir (M w 7.6), the 2009 Bhutan (M w 6.3) and the 2011 Sikkim (M w 6.9) earthquakes in different segments of the Himalayas and the 2016 Manipur (M w 6.7) earthquake in NE India region (e,g, Kayal 2008Rao et al, 2015;Singh et al, 2017 and references therein). Seismotectonics of the main shocks and aftershock sequences of the above strong / large earthquakes are well studied, that shed fair…”
Section: Seismicitymentioning
confidence: 99%